Level of emotion comprehension in children with mid to long term cochlear implant use: How basic and more complex emotion recognition relates to language and age at implantation. (August 2016) - Mancini, Patrizia; Giallini, Ilaria; Prosperini, Luca; D'alessandro, Hilal Dincer; Guerzoni, Letizia; Murri, Alessandra; Cuda, Domenico; Ruoppolo, Giovanni; De Vincentiis, Marco; Nicastri, Maria
Abstract: Objectives: The current study was designed with three main aims: To document the level of emotional comprehension skills, from basic to more complex ones, reached by a wide sample of cochlear implant (CI) deaf children with at least 36 months of device use; To investigate subjective and audiological factors that can affect their emotional development; To identify, if present, a "critical age", in which early intervention might positively affect adequate emotional competence development. Design: This is an observational cohort study. Children with congenital severe/profound deafness were selected based on: aged by 4–11 years, minimum of 36 months of CI use, Italian as the primary language in the family; normal cognitive level and absence of associated disorders or socio-economic difficulties. Audiological characteristics and language development were assessed throughout standardized tests, to measure speech perception in quiet, lexical comprehension and production. The development of emotions' understanding was assessed using the Test of Emotion Comprehension (TEC) of Pons and Harris, a hierarchical developmental model, where emotion comprehension is organized in 3 Stages (external, mental and reflective). Statistical analysis was accomplished via the Spearman Rank Correlation Coefficient, to study the relationship between the personal and audiological characteristics; a multivariate linear regression analysis was carried out to find which variables were better associated with the standardized TEC values; a chi-squared test with Yate's continuity correction and Mann-Whitney U test were used to account for differences between continuous variables and proportions. Results: 72 children (40 females, 32 males) with a mean age of 8.1 years were included. At TEC score, 57 children showed normal range performances (79.17% of recipients) and 15 fell below average (20.83% of recipients). The 16.63% of older subjects (range of age 8–12 years) didn't master the Stage 3 (reflective), which is normally acquired by 8 years of age and failed 2 or all the 3 items of this component. Subjects implanted within 18 months of age had better emotion comprehension skills. TEC results were also positively correlated with an early diagnosis, a longer implant use, better auditory skills and higher scores on lexical and morphosintactic tests. On the contrary, it was negatively correlated with the presence of siblings and the order of birth. The gender, the side and the severity of deafness, type of implant and strategy were not correlated. Conclusions: Early implanted children have more chance to develop adequate emotion comprehension, especially when the complex aspects are included, due to the very strong link between listening and language skills and emotional development. Furthermore, longer CI auditory experience along with early intervention allows an adequate communication development which positively influences the acquisition of such competencies.